Structural inhomogeneities in oxygen-deficient ErBa2Cu3O6+x associated with the tetragonal-to-orthorhombic transition: Evidence of first-order behavior. - Radaelli, P; Segre, C; Hinks, D; Jorgensen, J (1992)
Neutron powder diffraction and ac susceptibility data on a series of ErBa2Cu3O6+x samples prepared to achieve thermal equilibrium at low temperature provide evidence of structural inhomogeneities near the tetragonal-to- orthorhombic (T'O) transition. In the composition range 0.25x0.45, the data can best be described as a mixture of orthorhombic and tetragonal phases. This observation, together with the presence of discontinuities in the order parameters, leads to the conclusion that the T'O transition is first order in the temperature range where these samples were prepared. This interpretation provides a simple explanation for the differences between oxygen-deficient RBa2Cu3O6+x (R=Y, rare earths) samples prepared by different techniques. © 1992 The American Physical Society.